Plant MTs-long neglected members of the metallothionein superfamily - Freisinger, Eva (DALTON TRANSACTIONS, 2008)
Occurrence of metallothioneins (MTs) was initially thought to be restricted to the animal kingdom, and the corresponding functions such as detoxification of heavy metal ions were assumed to be taken over in plants by the enzymatically synthesized phytochelatins. This perception was revised in the past years, and the existence of plant metallothioneins is generally accepted. Compared to the vertebrate forms, members of the plant MT family display a significantly larger sequence diversity, however, surprisingly little information is available concerning their possible functions, properties, and structures. Gene expression studies, and thus studies on the mRNA level, are the major source of data aiming at elucidating the function of plant MTs. However, so far it is not possible to unambiguously assign a specific function to a given metallothionein as proposed functions overlap, are complementary to each other, or even contradictory results are obtained. With respect to the structures and properties of plant metallothioneins even less scientific contributions are available illustrating the early stages, in which this research area resides. Existing data covers the metal ion content of the different plant metallothionein species and the pH stabilities of the resulting metal-thiolate clusters. Further, for a limited selection of proteins the number of clusters formed has been proposed and predictions towards the secondary structure of the protein backbone made. A recently determined three-dimensional structure of the larger domain of the wheat metallothionein E(c)-1 describes a metal ion coordination mode unprecedented for any metallothionein so far.
APSAPSThe following values have no corresponding Zotero field: pub-location: THOMAS GRAHAM HOUSE, SCIENCE PARK, MILTON RD, CAMBRIDGE CB4 0WF, CAMBS, ENGLAND publisher: ROYAL SOC CHEMISTRY
Keywords: Heavy metals; plant metallothioneins

Plant MTs-long neglected members of the metallothionein superfamily (DALTON TRANSACTIONS, 2008)
Occurrence of metallothioneins (MTs) was initially thought to be restricted to the animal kingdom, and the corresponding functions such as detoxification of heavy metal ions were assumed to be taken over in plants by the enzymatically synthesized phytochelatins. This perception was revised in the past years, and the existence of plant metallothioneins is generally accepted. Compared to the vertebrate forms, members of the plant MT family display a significantly larger sequence diversity, however, surprisingly little information is available concerning their possible functions, properties, and structures. Gene expression studies, and thus studies on the mRNA level, are the major source of data aiming at elucidating the function of plant MTs. However, so far it is not possible to unambiguously assign a specific function to a given metallothionein as proposed functions overlap, are complementary to each other, or even contradictory results are obtained. With respect to the structures and properties of plant metallothioneins even less scientific contributions are available illustrating the early stages, in which this research area resides. Existing data covers the metal ion content of the different plant metallothionein species and the pH stabilities of the resulting metal-thiolate clusters. Further, for a limited selection of proteins the number of clusters formed has been proposed and predictions towards the secondary structure of the protein backbone made. A recently determined three-dimensional structure of the larger domain of the wheat metallothionein E(c)-1 describes a metal ion coordination mode unprecedented for any metallothionein so far.
APS